Modernity and interreligious dialogue. Difficulties posed by the ideological translation of religious categories - María A. Corpas-Aguirre (Warszawskie Studia Teologiczne)
The relationship between Islam and Modernity is often explained in antagonistic terms. On the one hand, because Islam is a holistic system, where the political and religious spheres remain connected, resisting a modern definition of “religion”. On the other, because Modernity has been associated with the evolution of the liberal State and democracy, whose bases are deeply relativistic. Along these lines, we propose some arguments about the origin of this disagreement. To do this, we focus on the ideological reductionisms “religion” and “state” applied to the theological categories Dīn and dawla. The trace of this modern homologation can be traced through the historical connection of the West with the Islamic Arab world. Enlightened approaches and their ideal of progress found their best expression in reformist thinking. Since the 18th century, the solution to the problems derived from colonialism necessarily went through making the dogmatic foundations more flexible, injecting sceptical principles. The birth of this “political Islam” necessarily brought its “national” translation. The processes of construction of these states would feed the liberation movements, spreading for decades the deep wound of political violence and its export to the world. It is from this context that the Catholic Church has appealed to theological foundations as the only possible way to reverse the damage caused by geopolitics. Unfortunately, the states of opinion generated around this work divide, in the first place, Catholics. Throughout these pages, we will try to provide lines of reflection that add to our responsibility to generate a Christian conscience, open, reasonable and without interference, with respect to Islam.